Treatment with long chain n-3 polyunsaturated fatty acids improves adipose tissue hypoxia and alters macrophage polarization in severely obese subjects - Zeyda, M; Itariu, BK; Neuhofer, A; Stulnig, TM (Experimental and clinical endocrinology & diabetes, 2012)
Introduction: Hypoxia is hypothesized to sustain adipose tissue inflammation and to initiate adipose tissue fibrotic remodeling, a newly found feature of obesity related pathological alterations. Relative adipose tissue hypoxia, which is characterized by increased expression of transcription factor HIF1-α (hypoxia inducible factor 1α) may facilitate the transition from M2 to proinflammatory M1 macrophage polarization. M1 macrophages produce high levels of chemokines which further recruit more macrophages to the tissue, promoting to the development of insulin resistance in humans. We hypothesized that long chain n-3 polyunsaturated fatty acids (PUFA) ameliorate adipose tissue inflammation, reduce adipose tissue hypoxia and may prevent adipose tissue remodeling. Methods : In a randomized controlled open-label clinical trial we treated 49 severely obese subjects (BMI >40kg/m 2 ) with either 3,3g/d highly purified n-3 PUFA or the same amount of butterfat as a control for eight weeks. At the end of the treatment elective bariatric surgery was performed, during which we collected visceral and subcutaneous adipose tissue samples. We quantified gene expression of HIF1A , CD40 , CD68 , CD163 , MRC1 and TGFB in all adipose tissue samples by real-time RT-PCR and normalization to ubiquitin. Statistical analyses of mean differences of ddCt values in each group were performed by one-way ANOVA, separately for visceral and subcutaneous adipose tissue. Results : We detected a significant reduction of gene expression of HIF1A and CD40 , a M1 macrophage marker, after n-3 PUFA treatment in subcutaneous adipose tissue (P<0,05, while expression of overall ( CD68 ) and M2 macrophage markers CD163 and MRC1 was not significantly changed between treatment groups. Interestingly, we found a significant positive correlation between expression of HIF1A and CD40 in visceral adipose tissue within the control and the n-3 PUFA group. Gene expression of the established pro-fibrotic marker TGFB was significantly downregulated in adipose tissue following n-3 PUFA treatment. Conclusion : Long chain n-3 PUFA reduce adipose tissue hypoxia and might prevent adipose tissue remodeling. The correlation between hypoxia and macrophage polarization substantially corroborates the hypothesis that by ameliorating hypoxia n-3 PUFA cause an anti-inflammatory shift in adipose tissue macrophage phenotype. Thus, the reduction of adipose tissue hypoxia could underlie the mitigation of adipose tissue inflammation by n-3 PUFA. This work was supported by the Austrian National Bank (P12735) and the by the Federal Ministry of Economy, Family and Youth and the National Foundation for Research, Technology and Development (all to T.M.S.).